Likuiditas dan Leverage terhadap Nilai Perusahaan Dimediasi Profitabilitas: Eksplorasi Peran Financial Technology sebagai variabel Moderasi - Intan Zoraya; Chairil Afandy; Ridwan Nurazi; Nia Herlina (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose – This study aims to analyze the impact of liquidity and leverage on firm value mediated by profitability and explore the role of financial technology as a moderating variable on the effect of liquidity and leverage on profitability.Methodology – The population of this study are banks listed on the Indonesia Stock Exchange. The sampling technique in this study was purposive sampling, which obtained a sample size of 24 banks. The data collection method uses annual data documentation techniques (annual report), obtaining 144 data. The data analysis method in this study is moderated-mediation regression analysis.Findings – This study found that liquidity and leverage affect profitability. This study also reveals that liquidity affects firm value, while leverage has no effect on firm value. Furthermore, this study is able to explain that profitability mediates the effect of liquidity and leverage on firm value. An important result of this study is that financial technology is proven to moderate the effect of liquidity and leverage on profitability.Originality/Novelty – The complexity of this research model enriches the empirical study of the role of financial technology as a moderating influence of liquidity and leverage on firm value mediated by profitability.Implications – This research can practically provide guidance for banking companies to increase firm value by starting and/or increasing collaboration with fintech companies because it is an opportunity for companies to increase profitability. In addition, banks can also collaborate through investing in fintech companies or creating their own fintech services.